hanges in Knowledge About Dental Caries After Education Using Dental Story Stickers (Upper Grade Students of SDN 02 Mulyosari Pagerwojo Tulungagung) - Tiarasari, Pranindya Rahma; Sugito, Bambang Hadi; Marjianto, Agus (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Caries or cavities are diseases of the hard tissue of the teeth. Caries can occur due to plaque on the surface of the teeth, sucrose content from food residue, and acidic bacteria which then cause demineralization so that the teeth become cavities. Problem statement: Based on the results of the examination, data was obtained that the average number of dental caries in upper-class students at SDN 02 Mulyosari was 4.6 so that it did not match the target of the 2015-2020 RAN for dental and oral health, namely the number of dental caries in children aged 12 years reached 1.26. Method: This type of research is descriptive research. With a total of 40 students as respondents. The measuring instrument used was a questionnaire sheet to see students’ knowledge about dental caries. The data analysis technique used in this study was to calculate the average answer from all upper-class students at SDN 02 Mulyosari Pagerwojo Tulungagung then the percentage and presented in table form. Results: The results of the study showed that the knowledge of senior students of SDN 02 was included in the good category. Conclusion: The level of knowledge of senior students of SDN 02 Mulyosari Pagerwojo Tulungagung after counseling was 81%, included in the good category.